Performance Indicators and Accountability in Portuguese Public Universities: Socio-Economic Perspective - Augusta Ferreira; Carlos Santos; Azevedo, G.; Judite Gonçalves; Oliveira, J. (Handbook of Research on Modernization and Accountability in Public Sector, 2018)
The public sector in Portugal has undergone major reforms, coercing institutions of higher education into greater transparency in accountability and performance indicators. The purpose of this chapter is to evaluate the level of disclosure of performance indicators by the Higher Education Institutions in Portuguese Public Universities, with a special emphasis on the obligatory nature and to evaluate if there are factors that influence the level of disclosure. This study was based on the content analysis of the management or activity reports of the 13 Portuguese public universities to calculate de level of disclosure, and used the quantitative analysis based on the Least-squares regression on the investigation of factors that influence the level of disclosure. According to the data obtained, it can be concluded that Portuguese Public Universities discloses performance indicators imposed by law and voluntarily, and it was verified that the level of disclosure is influenced by the variables dimension, financing from other sources of funding and the ranking of web of universities.